2006
DOI: 10.1111/j.1365-2044.2006.04715.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol/remifentanil vs sevoflurane/remifentanil for long lasting surgical procedures: a randomised controlled trial

Abstract: SummaryWe compared the haemodynamics, emergence and recovery characteristics of total intravenous anaesthesia using propofol ⁄ remifentanil with sevoflurane ⁄ remifentanil anaesthesia, under bispectral index guidance, in 103 patients undergoing surgical procedures lasting > 3.5 h. Time to tracheal extubation was significantly shorter in the propofol group than in the sevoflurane group (mean (SD) 8.3 (3.5) min vs 10.8 (4.6) min, respectively; p = 0.0024), but further recovery was comparable in both groups. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Total intravenous anesthesia with propofol and remifentanil did not reduce the incidence of PONV, although propofol is generally assumed to be antiemetic. Some reports have demonstrated that propofol with opioid did not reduce the incidence of PONV compared to balanced anesthesia with opioid 16,17,18,19. Longer duration of anesthesia was identified as a risk factor for PONV, similar to the previous study 3,20,21,22.…”
Section: Discussionsupporting
confidence: 77%
“…Total intravenous anesthesia with propofol and remifentanil did not reduce the incidence of PONV, although propofol is generally assumed to be antiemetic. Some reports have demonstrated that propofol with opioid did not reduce the incidence of PONV compared to balanced anesthesia with opioid 16,17,18,19. Longer duration of anesthesia was identified as a risk factor for PONV, similar to the previous study 3,20,21,22.…”
Section: Discussionsupporting
confidence: 77%
“…However, the usefulness of response entropy for the detection of impending arousal or its relation to surgical stimulation has not yet been determined. Comparing drug consumption in our study with that in other published reports using propofol-remifentanil infusion [3,16], we note that in our study the remifentanil infusion in both groups was nearly doubled, whereas the propofol dose was comparable.…”
Section: Discussionsupporting
confidence: 68%
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies investigated postoperative nausea and vomiting, with 371 patients receiving propofol and 354 patients receiving inhalational anaesthesia [10,19,20,22,24,25,28,30]. Propofol was associated with a significant reduction in postoperative nausea and vomiting (relative risk (95% CI) 0.446 (0.304-0.656) (p < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation